2014
DOI: 10.1152/japplphysiol.00354.2014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and artery function in humans: nonresponse and its relationship to cardiovascular risk factors

Abstract: The objectives of our study were to examine 1) the proportion of responders and nonresponders to exercise training in terms of vascular function; 2) a priori factors related to exercise training-induced changes in conduit artery function, and 3) the contribution of traditional cardiovascular risk factors to exercise-induced changes in artery function. We pooled data from our laboratories involving 182 subjects who underwent supervised, large-muscle group, endurance-type exercise training interventions with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
84
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 42 publications
14
84
1
Order By: Relevance
“…34 In the present study, we observed significant decreases in both total and Nox-mediated H 2 O 2 in the obese skeletal muscle extracellular environment post-training. Despite no AIT-induced changes in the traditional cardiovascular risk factors, we observed augmented microvascular endothelial function in the obese group, while apocynin no longer affected endothelial function post-training.…”
Section: Discussionsupporting
confidence: 59%
“…34 In the present study, we observed significant decreases in both total and Nox-mediated H 2 O 2 in the obese skeletal muscle extracellular environment post-training. Despite no AIT-induced changes in the traditional cardiovascular risk factors, we observed augmented microvascular endothelial function in the obese group, while apocynin no longer affected endothelial function post-training.…”
Section: Discussionsupporting
confidence: 59%
“…19,43 Improvements in endothelium-dependent function can occur independently of improvements in risk factors such as blood lipids, blood pressure, obesity, and glycemic control. 44,45 Although exercise training has been shown to improve vascular function in both animals and humans, these changes are rapidly lost after the cessation of training. 46 In patients with a recent myocardial infarction, 4 weeks of exercise training resulted in significant improvements in endothelium-dependent dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other vascular function tests, such as reactive hyperemia, flow-mediated dilatation (FMD) and infusion of vasodilators are useful in that they test mainly one vasodilating mechanism and the effect or role of only one or a few vasodilator compounds. Such tests therefore allow for more specific insight into vasoregulatory mechanisms than exercise and particularly FMD has been proven useful as predictor of cardiovascular disease (142). FMD is commonly measured in the brachial artery and assessed as the change in vessel diameter that occurs after a period of forearm occlusion induced by use of a cuff (57).…”
Section: The Effect Of Training On Flow-mediated Vasodilatationmentioning
confidence: 99%
“…FMD is commonly measured in the brachial artery and assessed as the change in vessel diameter that occurs after a period of forearm occlusion induced by use of a cuff (57). A large number of studies have been conducted in which the effect of training on FMD has been evaluated in different populations with an emphasis not only on individuals at risk for cardiovascular disease (142), but also in healthy young individuals (309,409). Cardiovascular risk groups generally experience marked improvements in FMD with exercise training (426) whereas the effects are less clear in young healthy controls (146).…”
Section: The Effect Of Training On Flow-mediated Vasodilatationmentioning
confidence: 99%